Efeito do tamanho de partícula na ensilabilidade e no valor nutritivo de silagens de cana-de-açúcar para bovinos de corte - Campos, Andressa Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed to determine the ideal average particle size for sugarcane silage and its use in animal feed. For this, two experiments were conducted. In experiment 1, experimental silos were used to evaluate the fermentative profile (0, 3, 7, 14, 28 and 56 days) of the silage with four different particle sizes, composing the following treatments: T5: sugarcane silage chopped to 5 mm; T10: sugarcane silage chopped to 10 mm; T15: sugarcane silage chopped to 15 mm and T20: sugarcane silage chopped to 20 mm. In the silages with 56 days of storage, were determined the dry matter losses and evaluated chemical composition and aerobic stability for 12 days. The yeast population and pH values were determined in 4, 8 and 12 days of air exposure. This experiment was carried out for two consecutive years, with the same variables. In the second experiment, sugarcane silages with the same particle size were stored in silos type surface, and used in diets for beef cattle feedlot. For evaluation of productive performance, nutrients intake, feeding behavior and selection index, were used 40 Nellore young bulls with 20 months of age and 395 ± 23 kg of initial body weight, confined for 99 days. For the study of ruminal fermentation and passage rate of the fiber, were used 8 Nellore young bulls with 24 months of age and 470 ± 34 kg of body weight, with ruminal cannula. The diets with different particle sizes of silages affected the nutrients intake, except for the neutral detergent fiber (NDF), besides the rumination and chewing times by animals, promoting preferential intake of diets fractions, but there was not effect for average daily gain, with an average gain of 1.49 kg.dia-1. Different particle sizes influence to fermentation characteristics and chemical composition of sugarcane silage, but this factor is not the only defining the silage quality. Higher particles size induces the diet selection by animals, with preferential intake of smaller ...

Objetivou-se determinar o tamanho médio de partícula ideal para a ensilagem da cana-de-açúcar e o uso na alimentação animal. Para isso, foram realizados dois experimentos. No experimento 1, silos experimentais foram utilizados para avaliar o perfil fermentativo (0, 3, 7, 14, 28 e 56 dias de armazenamento) das silagens com quatro diferentes tamanhos de partículas, que compuseram os seguintes tratamentos: T5: silagem de cana-de-açúcar picada a 5 mm; T10: silagem de cana-de-açúcar picada a 10 mm; T15: silagem de cana-de-açúcar picada a 15 mm e T20: silagem de cana-de-açúcar picada a 20 mm. Nas silagens com 56 dias de armazenamento foram determinadas as perdas de matéria seca e realizadas análises químicas, além da estabilidade aeróbia, por 12 dias. Com 4, 8 e 12 dias de exposição aeróbia, o crescimento da população de leveduras e os valores de pH foram determinados. Esse experimento foi realizado por dois anos consecutivos, sendo as mesmas variáveis analisadas. No segundo experimento, avaliaram-se silagens de cana-de-açúcar com os mesmo tamanhos de partículas, armazenadas em silos tipo superfície, e utilizadas em dietas para bovinos de corte em confinamento. Nas avaliações de desempenho produtivo, consumo dos nutrientes, comportamento ingestivo e índice de seleção foram utilizados 40 bovinos da raça Nelore, com 20 meses de idade e peso corporal inicial de 395 ± 23 kg, confinados por 99 dias. Para o estudo de parâmetros ruminais e taxa de passagem da fibra, foram utilizados 8 bovinos da raça Nelore, com 24 meses de idade e 470 ± 34 kg, com cânula ruminal. As dietas com diferentes tamanhos de partículas das silagens afetaram o consumo dos nutrientes, exceto para a fibra em detergente neutro, além dos tempos desprendidos com ruminação e mastigação pelos animais, promovendo consumos preferenciais das frações das dietas, mas não afetou o ganho de peso diário dos animais, com ganho médio de ...
Keywords: Bovino de corte - Nutrição; Cana-de-açúcar - Silagem; Ensilagem; Levedos; Particulas; Animal nutrition